THE CREATIVITY OF JOHN FOWLES - Fayzullaeva, Umida; Muhiddinova, Maftuna (Журнал иностранных языков и лингвистики, 2023)
This article is dedicated to the creativity of John Fowles. His first works are perceived as an unexpected artistic phenomenon, radically different from traditional English prose. He is a creator who aspires to experiments, hoping to update the form of the novel. And at the same time it is noted that Fowles consciously aspires to national realistic traditions. Both ratings are correct. Because in modern English literature in creativity is felt traditions to a greater extent than others, Fowles is supported by taking inspiration from it.